Covalent Functionalization of Bioengineered Polyhydroxyalkanoate Spheres Directed by Specific Protein-Protein Interactions - Wong, Jin Xiang; Gonzalez-Miro, Majela; Sutherland-Smith, Andrew J.; Rehm, Bernd H. A. (Frontiers in Bioengineering and Biotechnology, 2020)
Bioengineered polyhydroxyalkanoate (PHA) spheres assembled in engineered bacteria are showing promising potential in protein immobilization for high-value applications. Here, we have designed innovative streamlined approaches to add functional proteins from complex mixtures (e.g., without prior purification) to bioengineered PHA spheres directly harnessing the specificity of the SpyTag/SpyCatcher mediated protein ligation. Escherichia coli was engineered to assemble PHA spheres displaying the SpyCatcher domain while simultaneously producing a SpyTagged target protein, which was in vivo specifically ligated to the PHA spheres. To further demonstrate the specificity of this ligation reaction, we incubated isolated SpyCatcher-coated PHA spheres with cell lysates containing SpyTagged target protein, which also resulted in specific ligation mediating surface functionalization. An even cruder approach was used by lysing a mixture of cells, either producing PHA spheres or target protein, which resulted in specific surface functionalization suggesting that ligation between the SpyCatcher-coated PHA spheres and the SpyTagged target proteins is highly specific. To expand the design space of this general modular approach towards programmable multifunctionalization, e.g., one-pot construction of immobilized multienzyme cascade systems on PHA spheres, we designed various recombinant bimodular PHA spheres utilizing alternative Tag/Catcher pairs (e.g., SnoopTag/SnoopCatcher and SdyTag/SdyCatcher systems). One of our bimodular PHA spheres resulted in simultaneous multifunctionalization of plain PHA spheres in one-step with two differently tagged proteins in in vitro and ex vivo reaction conditions while remains functional. Our bimodular PHA spheres also showed low orthogonality with the non-target peptide tag and exhibited decent robustness against repeated freeze−thaw treatment. We demonstrated the utility of these approaches by using a fluorescent protein, a monomeric amylase, and a dimeric organophosphate hydrolase as target proteins. We established a versatile toolbox for dynamic functionalization of PHA spheres for biomedical and industrial applications.